Reducing Return of Fear: The Dual Role of the Unconditioned Stimulus in the Acquisition and Long-lasting Reduction of Fear in Humans - Thompson, Alina (Curtin University, 2019)
This experimental research provided new insights into mechanisms mediating the enduring reduction of fear. The findings are of relevance to the basic and applied setting, demonstrating that fears that are typically difficult to treat can be attenuated through methods that involve exposure to the feared cues and the feared outcomes. Occasionally reinforced extinction training and behavioural reconsolidation interference prevented the return of fear by enhancing extinction learning and updating the content of consolidated memories, respectively.